New Strategies and Practices of Design Education Under the Background of Artificial Intelligence Technology: Online Animation Design Studio - Tang, Tianran; Li, Pengfei; Tang, Qiheng (Frontiers in Psychology, 2022)
this study is based on the background of how artificial intelligence (AI) technology is applied to the field of creativity and design education to improve the design vision, teaching methods and actual design productivity of practitioners. The purpose of the research is to compare traditional design education and new design education methods combined with artificial intelligence technology, Taking the TPACK technology integration model as the starting point, comprehensive evaluation is selected for different types of research,explore the animation design professional courses in design education, the content of students’ perception preferences, and the evaluation of ease of learning, so as to conduct research and analyze artificial intelligence technology. Design new education strategies and practice methods under the background. In the research, a comparative experimental study was conducted on 40 first-year students majoring in animation design. The results show that through online design studio project practice, with personalized project learning guidance, students' learning needs show a better trend, and customized learning and project practice content can enhance students' learning experience and performance. In the future, we can further expand the scope of analysis, include more case studies, and conduct more comprehensive research, including how to deal with the expansion of the platform for students’ learning of design in situations similar to COVID-19 that profoundly affects our lives, and how the project is Application in practice.